Dari Krisis Ruang Publik ke Kemitraan Intersektoral:Studi Kasus di RPTRA Kalijodo, Jakarta - Rakhmat Hidayat; Ayuningtyas Suciani Utari (JURNAL SOSIAL HUMANIORA (JSH), 2018)
This article discusses about the partnership between stakeholders in managing Child-Friendly Integrated Public Space (RPTRA) in Kalijodo, West Jakarta. Researchers use the Child-Friendy Integrated Public Space concepts, stakeholder concepts, and partnership stakeholder concepts. This article will explain about the roles and relations of stakeholders in managing RPTRA Kalijodo, also the implications of the relation between stakeholders in managing that RPTRA. Partnerships between stakeholders that involved in RPTRA Kalijodo include the division of roles, cooperation, and collaboration between the local government and the surrounding society as an effort to manage the RPTRA Kalijodo. The existence of that relation can be a partnership between stakeholders that involved, so the management of the RPTRA can run optimally and RPTRA Kalijodo can be utilized by the society.